Velo-Cardio-Facial Syndrome: 30 Years of Study - Shprintzen, Robert J. (2008)
Velo-cardio-facial syndrome is one of the names that has been attached to one of the most common multiple anomaly syndromes in humans. The labels DiGeorge sequence, 22q11 deletion syndrome, conotruncal anomalies face syndrome, CATCH 22, and Sedlačková syndrome have all been attached to the same disorder. Velo-cardio-facial syndrome has an expansive phenotype with more than 180 clinical features described that involve essentially every organ and system. The syndrome has drawn considerable attention because a number of common psychiatric illnesses are phenotypic features including attention deficit disorder, schizophrenia, and bipolar disorder. The expression is highly variable with some individuals being essentially normal at the mildest end of the spectrum, and the most severe cases having life-threatening and life-impairing problems. The syndrome is caused by a microdeletion from chromosome 22 at the q11.2 band. Although the large majority of affected individuals have identical 3 megabase deletions, less than 10% of cases have smaller deletions of 1.5 or 2.0 megabases. The 3 megabase deletion encompasses a region containing 40 genes. The syndrome has a population prevalence of approximately 1:2,000 in the U.S., although incidence is higher. Although initially a clinical diagnosis, today velo-cardio-facial syndrome can be diagnosed with extremely high accuracy by fluorescence in situ hybridization (FISH) and several other laboratory techniques. Clinical management is age dependent with acute medical problems such as congenital heart disease, immune disorders, feeding problems, cleft palate, and developmental disorders occupying management in infancy and preschool years. Management shifts to cognitive, behavioral, and learning disorders during school years, and then to the potential for psychiatric disorders including psychosis in late adolescence and adult years. Although the majority of people with velo-cardio-facial syndrome do not develop psychosis, the risk for severe psychiatric illness is 25 times higher for people affected with velo-cardio-facial syndrome than the general population. Therefore, interest in understanding the nature of psychiatric illness in the syndrome remains strong.